Safety In Mining - A Panel Discussion of Coal Mine Safety - Wednesday Morning, July 1 (Rocky Mountain Coal Mining Institute, 1953)
The final session on Wednesday morn¬ing was given over to a panel discussion of safety questions submitted by members of the institute. Mr. Murray presided, and Lyman Fearn, chief, Wyoming Dept. of Mines & Minerals, Rock Springs, Wyo., was moderator. Members of the panel were: John A. Garcia, chief mine inspector, New Mexico; Leonard Ford, mine foreman, Frederick- mine, CF&I, Valdez, Colo.; A. C. Moschetti, chief, coal mine inspection branch, USBM, Denver; Kirk V. Cammack, mining engineer, USGS, Denver; Joel N. Van Sant, chief engineer, St. Louis, Rocky Mountain & Pacific Coal Co., Raton, N. M.; Emery Olsen, safety engineer, coal mine and quarries, U. S. Steel Corp., Dragerton, Utah; F. J. Peternell, safety engineer, Union Pacific Coal Co., Rock Springs; and J. J. Reddy, mine inspector, Colorado Dept. of Mines, Grand Junction, Colo. On a question concerning the effect of roof-bolting on the maintenance of a breakline in pillar removal, Mr. Van Sant reported that some experience at his company's mines indicate that wood supports are not necessary to make the break although shooting is sometimes done to get it. Furthermore, bolting improves the roof in these pillar areas and extraction has increased about 20%. Mr. Fearn concurred in describing operations in parts of Wyoming.